Evaluation of Phenotypic and Genotypic Methods for Subtyping Campylobacter jejuni Isolates from Humans, Poultry, and Cattle - Nielsen, Eva Møller (American Society for Microbiology, 2000)
Six methods for subtyping of Campylobacter jejuni were compared and evaluated with a collection of 90 isolates from poultry, cattle, and sporadic human clinical cases as well as from a waterborne outbreak. The applied methods were Penner heat-stable serotyping; automated ribotyping (RiboPrinting); random amplified polymorphic DNA typing (RAPD); pulsed-field gel electrophoresis (PFGE); restriction fragment length polymorphisms of the flagellin gene, flaA (fla-RFLP); and denaturing gradient gel electrophoresis of flaA (fla-DGGE). The methods were evaluated and compared on the basis of their abilities to identify isolates from one outbreak and discriminate between unrelated isolates and the agreement between methods in identifying clonal lines. All methods identified the outbreak strain. For a collection of 80 supposedly unrelated isolates, RAPD and PFGE were the most discriminatory methods, followed by fla-RFLP and RiboPrinting. fla-DGGE and serotyping were the least discriminative. All isolates included in this study were found to be typeable by each of the methods. Thirteen groups of potentially related isolates could be identified using a criterion that at least four of the methods agreed on clustering of isolates. None of the subtypes could be related to only one source; rather, these groups represented isolates from different sources. Furthermore, in two cases isolates from cattle and human patients were found to be identical according to all six methods.